Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4238/2015.june.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in exons 4 and 10 of the BPI gene and immune indices in Sutai pigs

Abstract: ABSTRACT. The bactericidal/permeability-increasing protein (BPI) gene has been identified as a candidate gene for disease-resistance breeding. We evaluated whether polymorphisms in exons 4 and 10 of the BPI gene are associated with immune indices [interleukin-2 (IL-2), IL-4, IL-6, interferon-b (IFN-b), . In this study, we identified one mutation (C522T) in the BPI exon 4 site and two mutations (A1060G and T1151G) in the BPI exon 10 site. Correlation analysis revealed that in the Sutai pig population, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In this study, the polymorphism distribution of exon 10 in the BPI gene was detected in Meishan pigs. There were 3 genotypes, of which A was the predominant allele, which is consistent with the results of Wu et al (15). The suitability test results showed that HpaII polymorphisms of exon 10 in the BPI gene deviated from Hardy-Weinberg equilibrium (P < 0.01).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the polymorphism distribution of exon 10 in the BPI gene was detected in Meishan pigs. There were 3 genotypes, of which A was the predominant allele, which is consistent with the results of Wu et al (15). The suitability test results showed that HpaII polymorphisms of exon 10 in the BPI gene deviated from Hardy-Weinberg equilibrium (P < 0.01).…”
Section: Discussionsupporting
confidence: 90%
“…Studies investigating the cytokines Interferon (IFN)- γ and IL-10 used vaccination with Mycoplasma hyopneumoniae , tetanus toxoid, the porcine reproductive and respiratory syndrome virus (PRRSV) [ 39 , 40 ] and the classical swine fever virus [ 41 , 42 ]. Another study analysing cytokines, including IL-6 and IL-12, was restricted to exonic regions of a single gene [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 has extensive capacity to activate cytotoxic lymphocytes, including Th1-mediated CD4+ cell differentiation, and stimulates the activation of natural killer (NK) cells and the production of INF-γ 43 ; therefore, it has been considered a target gene for bioprevention. Wu et al 44 demonstrated that the higher expression of IL-6 or IL-12 contributed to improving the general disease resistance in pigs 44 . Thus, we speculated the CD14 gene probably represents an important candidate gene related to the resistance to E. coli F18 in Chinese Meishan pigs.…”
Section: Discussionmentioning
confidence: 99%